Thin Layer Chromatography (TLC) Fingerprint Analysis of Moringa oleifera Leaves Extract - Jayani, Nikmatul Ikhrom Eka; Jaya , I Gusti Ngurah Sutan; Martins, Merliana Putri Pratiwi; Rani, Karina Citra (MPI (Media Pharmaceutica Indonesiana), 2025)
Moringa oleifera is known to be rich in nutrients and phytochemicals. M.oleifera is also widely used for herbal medicine and functional food. Fingerprint profiling is one of the methods used to determine the quality and authenticity of M.oleifera leaves and prevent counterfeiting. The study aimed was to determine optimal chromatographic parameters (stationary and mobile phases, blot volume, and detection method) capable to generating the highest number of bands with good separation. The method used was Thin Layer Chromatography (TLC), accompanied by stability testing and precision testing. The results showed that fingerprint profile of M. oleifera leaves, created using the mobile phase toluene: ethyl acetate: methanol: formic acid (7:2:1:0.2), stationary phase TLC plate with silica gel 60 F254. Test solution was 70% ethanol viscous extract of M. oleifera leaves, dissolved in methanol with a blotting volume of 5μl, observed in UV 366 nm and obtained eight bands. Stability and precision testing of the TLC condition optimization method showed that the analyte was stable on the TLC plate and in solution. The analyte also showed stability results during the chromatography process, and the repeatability and intermediate precision were met the criteria. The TLC fingerprint analysis method with chromatographic conditions optimized in this study can be used as one of the quality control methods of M. oleifera leaf raw materials.